SUSTAINABLE WATER SOLUTIONS FOR RURAL AREAS USING SOLAR HYBRID SYSTEMS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The issue of water supply in rural areas has remained a pressing problem for many years. The limited availability of Water Resources and their uneven distribution, as well as natural disasters and climate changes, make it difficult to ensure the stability of the water supply. These problems limit the ability of the villagers to obtain sufficient water needed for health, agriculture and daily life. Therefore, the creation and application of sustainable and environmentally friendly water supply systems is important for the development of rural areas. Solar hybrid systems are seenas an effective solution for precisely these purposes.